2020
DOI: 10.1080/0284186x.2020.1813326
|View full text |Cite
|
Sign up to set email alerts
|

The majority of Danish breast cancer survivors on adjuvant endocrine therapy have clinically relevant sexual dysfunction: a cross-sectional study

Abstract: Background: Impairments in sexual function are common among breast cancer survivors (BCSs), particularly in BCSs receiving adjuvant endocrine therapy (AET). Whether these impairments cause distress, thus qualifying for a more clinically relevant diagnosis of sexual dysfunction (SD), is inadequately described among BCSs and represents an important research gap. Hence, the primary aim of this study was to estimate the prevalence of clinically relevant SD, in this context: impairments with associated distress, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
0
13
1
4
Order By: Relevance
“…FSD, as classified by the FSFI, was identified in 61.2% of the sexually active patients within our study sample. A cross-sectional study which similarly applied the FSFI solely in sexually active breast cancer patients on ET and used the cut-off score of ≤26.55 reported FSD in 63% (142/227) of their study sample [32]. When comparing FSFI domain scores by ET type, we observed no significant differences, which is inconsistent with previous observational studies evaluating the symptoms covered by these domains [16].…”
Section: Discussioncontrasting
confidence: 99%
“…FSD, as classified by the FSFI, was identified in 61.2% of the sexually active patients within our study sample. A cross-sectional study which similarly applied the FSFI solely in sexually active breast cancer patients on ET and used the cut-off score of ≤26.55 reported FSD in 63% (142/227) of their study sample [32]. When comparing FSFI domain scores by ET type, we observed no significant differences, which is inconsistent with previous observational studies evaluating the symptoms covered by these domains [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Treatment for stage I–III BC is often intense including combinations of surgery, radiotherapy, and adjuvant systemic therapies (endocrine therapy, chemotherapy, and targeted therapy), which may have a negative impact on sexual health [ 8 10 ]. Studies have focused on various aspects of sexual health, like sexual activity, interest, enjoyment and discomfort, and reported that sexual health impairments are prevalent among BCSs both during treatment and during the first years after diagnosis [ 11 15 ]. However, it remains unclear if these sexual health impairments persist long-term (> 5 years after diagnosis), as data from this part of survivorship are scarce and results conflicting [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates differ, however, widely across studies from 27% [14] to 93% [15], primarily reflecting methodological differences. Most studies focus on sexual health during the first few years after BC diagnosis [15][16][17][18][19] and therefore research-based knowledge concerning sexual health among long-term BCSs is limited [20][21][22][23][24]. Furthermore, how different BC treatments (surgery, chemotherapy, and endocrine therapy) contribute to sexual dysfunction at long term is still unclear [5,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%